Implementation Of Religious Justice In Marketing The Products Of Central Java's Muhammadiyah Business Charities - Juma'i Juma'i; Yustinah Yustinah (PT. Publikasiku Academic Solution, 2024)
The implementation of religious justice in Muhammadiyah Charity (AUM) can be seen from the perspective of its muamalah. Muhammadiyah Charity (AUM) provides benefits not only from which company is an Indonesian citizen and is Muslim or not. In Managerial, it is very open to be able to join both as an employee and as a control holder of the management of the Muhammadiyah Business Charity. The type of research used is field research, The subject in this study is Muhammadiyah charity (AUM) Central Java, The type of data needed in this study consists of primary data and secondary data, data collection methods with Interview or Interview Method, observation and documentation, Data analysis used is non-statistical analysis but with descriptive analysis. The implementation of religious justice in the marketing of Muhammadiyah charity products goes hand in hand with the vision and mission of an independent organization and moves in amar makruf nahi munkar. good management and management of the organization and employee performance based on the One and Only God and justice for all Indonesian people. The marketing of Muhammadiyah Charity products with religious justice can be seen from the way employees and partners are recruited, all are very open and can take part, not necessarily from within a certain company or organization. Equality and equality as part of religious justice can be based on the philosophy of ta'awun.